RELIGION BASED CHARACTER EDUCATION TOWARDS A MENTAL REVOLUTION - Nadwa Farhati; Ahmad Faroji; H.M. Luthfi (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
Character education is a process of guiding students to become whole individuals with character encompassing the dimensions of heart, mind, body, feelings, and intentions.It can be understood as value education,moral education,and character formation aimed at enabling individuals to distinguish between right and wrong, maintain goodness, and practice it sincerely in daily life. Thus, character education is viewed as a system of norms and values manifested in various forms of personal qualities. Personal character is grounded in noble values that are ultimately reflected in behavior. Therefore, education that develops character plays a crucial role in fostering ethical attitudes, morality, and responsibility.The method used in this study is library research, in which the authors utilize books and academic journals as references. The literature is selected based on its relevance to the topic and supported by existing empirical studies related to religion-based character education. Character values such as honesty, justice, trustworthiness, wisdom, modesty, responsibility, courage, discipline, independence, compassion, tolerance, patriotism, and other noble moral values are derived from religious teachings. Furthermore, religion holds a fundamental position in the life of the Indonesian nation. The implementation of religion-based character education in schools is highly effective in shaping students’ character as future generations.